(untitled) (Research, Society and Development, 2021)
Objective: To analyze governmental recommendations and scientific evidence regarding the use of respiratory protectors by health professionals in the context of the SARS-CoV-2 pandemic. Method: Scoping Review, following the protocol proposed by the Joanna Briggs Institute (JBI), Version 2020. The PCC (Population, Concept and Context) strategy was used to formulate the following guiding question: “What are the recommendations regarding the use of masks? Respiratory protection respirators by health professionals facing the risk of contamination by SARS-CoV-2? ”. Searches were carried out in six international databases and in gray literature and on government websites in different countries, from July to August 2020. Results: 20 studies published in 2020 were included. On the methodology of the studies, 1 (5%) study descriptive, 1 (5%) narrative review, 2 (10%) systematic review with meta-analysis, 2 systematic reviews (10%), 8 (40%) literature review and 6 (30%) technical report. Conclusion: There are differences regarding: type of respiratory protection in routine care, when there is no generation of aerosols, with studies that indicate the use of surgical masks and others that recommend the use of a particulate respirator; there is an indication of different particulate respirators of varying degrees of protection, for the same scenario of clinical exposure, and there is conflict regarding the scenario of greater exposure for health professionals, in disagreement of which procedures generate aerosols.